2001
DOI: 10.1097/00129492-200109000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Otologic Manifestations of Chiari I Malformation

Abstract: Most patients with Chiari I malformation have symptoms that mimic primary otologic pathologic changes. The existence of common pathophysiologic mechanisms is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…Analysis of the absolute latency values in patients with Chiari malformation type II disclosed a tendency to increased median value of potentials III and V when compared to normal values ( Table 1). The most plausible explanation for this discre p a n c y is that it is probably due to the association of type II brainstem abnormalities and the sensory-neural maturation delay typically found in this kind of malformation 5,11,12 .…”
Section: Graphic 1 Abnormalities Found In the Auditory Pathway Absomentioning
confidence: 99%
“…Analysis of the absolute latency values in patients with Chiari malformation type II disclosed a tendency to increased median value of potentials III and V when compared to normal values ( Table 1). The most plausible explanation for this discre p a n c y is that it is probably due to the association of type II brainstem abnormalities and the sensory-neural maturation delay typically found in this kind of malformation 5,11,12 .…”
Section: Graphic 1 Abnormalities Found In the Auditory Pathway Absomentioning
confidence: 99%
“…Other studies support the notion that headache and neck pain are frequent complaints, occurring in 65% to 81% of patients; however, sufficient characteristics of headaches are lacking [26][27][28][29].…”
Section: Asymptomatic and Headache Clinical Presentationsmentioning
confidence: 89%
“…Sperling et al [29] reported otologic CMI symptoms in 16 patients who were observed prospectively. On a selfadministered questionnaire, 81% of the patients reported episodic aural fullness, 81% tinnitus, 69% vertigo, 56% fluctuating hearing loss, and 81% headaches.…”
Section: Other Clinical Presentationsmentioning
confidence: 99%
“…Cranial nerve dysfunction is common in Chiari I [59,88], and auditory brainstem response (ABR) findings in Chiari II are consistent with delayed brainstem maturation and progressive cochlear nerve stretching [79,84]. Several studies have found evidence for a hydrodynamic cause of hearing loss; symptoms of endolymphatic hydrops have been reported in Chiari I [4,74,107], and one study found hydrocephalus to be an independent predictor of hearing loss, distinct from the presence of cranial nerve deficits [65]. However, Chiari malformation-related hearing loss is likely multifactorial in origin.…”
Section: Auditory Pathway Dysfunctionmentioning
confidence: 99%
“…Auditory or vestibular symptoms have been reported in 74 % of patients with Chiari I [74] and 57-69 % of patients with Chiari II [12,126]. Proposed etiologies of hearing loss include cranial nerve stretching, compression of the cochlear nerve or nuclei by the cerebellar tonsils, and transmission of abnormal CSF pressures to the inner ear [2,31,49,53,107]. Cranial nerve dysfunction is common in Chiari I [59,88], and auditory brainstem response (ABR) findings in Chiari II are consistent with delayed brainstem maturation and progressive cochlear nerve stretching [79,84].…”
Section: Auditory Pathway Dysfunctionmentioning
confidence: 99%